ANALYSIS OF THE RELATION BETWEEN GLOBAL CONSUMER CULTURE AND MATERIALISM - Ercan KESER (Fırat University, 2019)
Globalization is spreading rapidly through the world, shaping people’s daily lives and affecting their attitudes and behaviors. Global media, mass migration, advancements in technology and international business are accelerating the rising up of the global consumer culture by creating a homogenized world market with similar preferences, needs and wants. Global consumer culture as a cultural entity not associated with a single country, but rather a larger group generally recognized as international and transcending in